Percepción de la contaminación y ciudadanía ambiental en la población del distrito de Iquitos, Maynas, Loreto, 2022 - Llucema Mori, Erick Junior (2023)
This research aims to determine the relationship between the perception of pollution and environmental citizenship in the population of the district of Iquitos, Maynas, Loreto 2022. The research has a quantitative approach, the type of study is descriptive, observational, prospective; cross-sectional and analytical, the hypothetical-deductive method was used. 97.1% indicate that there is pollution by domestic waste in the district, 93.7% that the landscape of the district was negatively modified, generating that 80.7% present stress and bad mood, 90.9% do not receive awareness talks on environmental issues, 70% do not know the existence of OEFA or the functions they perform, and 97.1% ask for severe sanctions to bad citizens for non-compliance with the rules, 98.4% consider that the municipality should also be severely sanctioned for breach of its responsibilities. A statistically significant relationship (Rho = - 0.110 and p = 0.034) is determined between the perception of pollution and environmental citizenship, that is, the greater the environmental citizenship in the population of the district, the lower the pollution by solid waste, the perception of pollution resulted in 59.5% of inadequate level and environmental citizenship was with 86.2% of moderate level, it is determined that there is a significant statistical relationship (Rho = -0.174 and p = 0.001) between the perception of pollution and the dimension municipal environmental responsibility, that is, the cause of the problem is due to lack of the principle of authority that the municipality must impose and not adequately comply with its environmental management policy.